Transformational Leadership style: an important ingredient for the Socio-economic Sustainability of service SMEs in Cameroon - FOKAM , Jeff Astein Mbah (Revue Internationale des Sciences de Gestion, 2023)
The principal objective of this research is to evaluate the impact of the Transformational Leadership styles on the Socio-economic Sustainability of SMEs in the service sector in Cameroon. To realize the above-cited objective, this research is based on the philosophical underpinnings of positivism epistemology and objectivism ontology, the study hence adopted a hypothetico-deductive approach from which data was collected using a semi-structured questionnaire from 531 respondents from 169 SMEs in the service sector from 05 regions of Cameroon, Structural equation models were used to demonstrate the causality between the two concepts with the help of Amos version 23 software. The main findings indicate that the transformational leadership style has a positive and insignificant effect. (with a P-value = 0.306 > 0.05) on Socio-economic sustainability of SMEs and suggests that SME should put more accents on a mutually beneficial exchange, to ensure a satisfactory relationship with the social partners and hence Sustainability while reinforcing the Transformational leadership style to build and share a long term vision with the workers.